First record for México of the whitefly Aleuroparadoxus Arctostaphyli Russell, 1947, (hemiptera: aleyrodidae) hosts, distribution and parasitoid - Sánchez-Flores, Óscar Ángel; García Martínez, Oswaldo; Carapia-Ruiz, Vicente Emilio (Instituto de Ecología, A.C., 2017)
The first record for Mexico of the whitefly Aleuroparadoxus arctostaphyli Russell, with data on hosts, its distribution and a parasitoid is presented.